Halitosis - oral malodour - Greenman, John (Henry Stewart Talks, 2017)
Background and early work on oral malodour from the 1970’s onwards, Measurement of oral malodour using the human nose and analytic instruments, Role of tongue biofilm microbes and periodontal disease in malodour, Interventions: oral hygiene (tongue surface cleaning), chemo-preventative measures and periodontal treatment